ANALYSIS OF FACTORS INFLUENCING NURSE COMPLIANCE IN EARLY WARNING SCORE MONITORING IN PATIENTS IN THE INPATIENTS ROOM OF RSIA DEDARI KUPANG - Jodjana, Kevin; A Manafe, Henny; Perseveranda, M.E.; Sia Niha, Simon (JURNAL EKBIS, 2024)
Nurse compliance plays an important role in supporting patient safety with an attitude of having to respond quickly and act. The type of data used in this study is quantitative data using statistics, with the aim of testing the established hypothesis in the form of a questionnaire. The research sample used was all inpatient nurses at RSIA Dedari Kupang totaling 40 people. The data analysis technique in this study used descriptive statistics and inferential statistics in the form of a list of statements arranged based on indicators from each variable tested including nurse compliance, nurse attitudes, nurse knowledge, nurse motivation, nurse age, nurse work experience, and nurse Early Warning Score training. With a research period from August 2023 to January 2024. The research tool uses the SPSS application.